Binder for secondary battery, slurry containing same, electrode, and secondary battery

By adjusting the degree of hydrolysis of water-soluble monomers and optimizing the ratio of conductive monomer to copolymer in the secondary battery binder, the challenges of aggregation and reduced conductivity in existing conductive polymers are addressed, resulting in enhanced battery performance.

JP2025510218AActive Publication Date: 2025-04-14HANSOL CHEM +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024556611
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-25
Filing Date
2022-04-01
Publication Date
2025-04-14
Estimated Expiration
2042-04-01

AI Technical Summary

Technical Problem

Existing water-soluble monomers used in the production of conductive polymers for secondary batteries face challenges such as aggregation, reduced electrical conductivity, and poor slurry rheology due to increased PEDOT content.

Method used

A secondary battery binder containing a conductive polymer is developed, where the degree of hydrolysis of a water-soluble monomer is adjusted to 50% or more, and a specific ratio of conductive monomer to second copolymer is used, improving dispersibility and electrical conductivity.

Benefits of technology

The binder achieves high dispersion and electrical conductivity, leading to improved electrode performance and extended battery life with reduced internal resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510218000001_ABST
    Figure 2025510218000001_ABST
Patent Text Reader

Abstract

The present invention includes a water-soluble polymer and a conductive polymer, the water-soluble polymer includes a first copolymer, the conductive polymer includes a second copolymer and a polymer of a conductive monomer, the second copolymer has a degree of hydrolysis of 50% or more, and has a peak at 3250 cm in an FT-IR spectrum. -1 Or 3350cm -1 The present invention provides a binder for secondary batteries, in which an absorbance peak appears at 22% or more, and a slurry, electrode, and secondary battery each containing the binder.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a binder for secondary batteries including a conductive polymer, a slurry including the same, an electrode, and a secondary battery. More specifically, the present invention relates to a binder for secondary batteries including a conductive polymer that can realize excellent characteristics by controlling the degree of hydrolysis of a water-soluble monomer used in manufacturing the conductive polymer for secondary batteries, and a slurry, an electrode, and a secondary battery including the same. [Background technology]

[0002] Lithium batteries are used as power sources for portable electronic devices such as video cameras, mobile phones, laptops, etc. Rechargeable lithium secondary batteries have an energy density per unit weight that is more than three times higher than existing lead-acid batteries, nickel-cadmium batteries, nickel-metal hydride batteries, nickel-zinc batteries, etc., and can be charged quickly.

[0003] In general, a lithium secondary battery is manufactured by using a material capable of reversible intercalation and deintercalation of lithium ions as a positive electrode active material and a negative electrode active material, and filling an electrolyte between a positive electrode containing the positive electrode active material and a negative electrode containing the negative electrode active material.

[0004] Meanwhile, among electrode materials, the binder plays a major role in maintaining the electrode plate structure, but it can also affect the properties of the electrode and lithium secondary battery manufactured using it. Water-soluble conductive polymers can be added to improve the binder's performance, but the existing water-soluble monomers used to manufacture water-soluble conductive polymers have the disadvantages of poor processability and reduced electrical conductivity due to the generation of agglomeration and reduced dispersing power when the content of PEDOT in the polymer increases, and the viscosity decreases as the content of PEDOT increases during slurry production, adversely affecting the rheology of the slurry. In addition, conductive polymers with excellent dispersing power are easy to process, but their low electrical conductivity can reduce the electrical conductivity in the electrode, affecting electrode performance. Therefore, there is a need to research conductive polymers that can overcome these disadvantages. Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made to solve the problems of the prior art, and it is an object of the present invention to provide a binder for secondary batteries including a conductive polymer that can realize excellent properties by controlling the degree of hydrolysis of a water-soluble monomer used in the preparation of a conductive polymer for secondary batteries, and a slurry, electrode, and secondary battery including the same. [Means for solving the problem]

[0006] The binder for a secondary battery according to an embodiment of the present invention includes a water-soluble polymer and a conductive polymer, the water-soluble polymer includes a first copolymer, the conductive polymer includes a second copolymer and a polymer of a conductive monomer, the second copolymer has a degree of hydrolysis of 50% or more, and has a peak at 3250 cm in an FT-IR spectrum. -1 Or 3350cm -1 The absorbance peak may be 22% or more.

[0007] The first copolymer may be a copolymer of a polymer containing a polar functional group and a PAA, and may have an uncontrolled degree of hydrolysis. The first copolymer may be a PVA-PAA having an uncontrolled degree of hydrolysis.

[0008] The second copolymer may be a copolymer of a polar functional group-containing polymer and PAA with a controlled degree of hydrolysis. The second copolymer may be a PVA-PAA with a controlled degree of hydrolysis.

[0009] The conductive monomer may be at least one selected from the group consisting of EDOT (3,4-Ethylenedioxythiophene), a thiophene-based monomer, polyacetylene, polyaniline, and polypyrrole.

[0010] The conductive polymer may include a weight ratio of conductive monomer to second copolymer of 1:0.5 to 20. The conductive polymer may include a weight ratio of conductive polymer to water-soluble polymer of 4 to 6:1.

[0011] The slurry according to an embodiment of the present invention may include an electrode active material and the binder described above.

[0012] Based on 100% by weight of the total slurry, the slurry may contain 95 to 99% by weight of the electrode active material and 1 to 5% by weight of the binder.

[0013] The electrode according to an embodiment of the present invention may be formed by coating the above-described slurry on a surface of a current collector and drying it.

[0014] The secondary battery according to an embodiment of the present invention includes a positive electrode, a negative electrode, an electrolyte interposed therebetween, and a separator interposed between the positive electrode and the negative electrode, and at least one selected from the positive electrode and the negative electrode may be the above-mentioned electrode. Effect of the Invention

[0015] The binder for secondary batteries including the conductive polymer according to the embodiment of the present invention has the characteristics of high dispersion and high electrical conductivity.The slurry according to the embodiment of the present invention has excellent dispersion stability. The electrodes according to the embodiments of the present invention have excellent electrode conductivity, and the secondary batteries according to the embodiments of the present invention have improved internal resistance and life characteristics. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a graph showing the degree of hydrolysis of PAA-1 and PAA-5 prepared in the Preparation Examples of the present invention, measured by FT-IR. [Diagram 2] FIG. 2 is a photograph confirming the presence or absence of phase separation in the conductive polymer binders of Example 2 of the present invention and Comparative Example 2. [Diagram 3] FIG. 3 is a photograph showing the dispersion stability of the slurries of Comparative Example 1, Comparative Example 2, Example 1, and Example 2 of the present invention evaluated using a grind gauge. [Figure 4] FIG. 4 is a graph showing the results of electrochemical evaluation of the lithium secondary batteries of Comparative Example 1, Comparative Example 2, Example 1, and Example 2 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Terms such as first, second and third are used to describe various parts, components, regions, layers and / or sections, but are not limited thereto. These terms are used only to distinguish one part, component, region, layer or section from another part, component, region, layer or section. Thus, a first part, component, region, layer or section described below can be referred to as a second part, component, region, layer or section without departing from the scope of the present invention. The terminology used herein is merely for the purpose of describing a particular embodiment and is not intended to limit the present invention. The singular form used herein includes the plural form unless the context clearly indicates otherwise. The term "comprising" as used in the specification embodies a particular feature, region, integer, step, operation, element and / or component and does not exclude the presence or addition of other features, regions, integers, steps, operations, elements and / or components. When a part is "on" or "on" another part, this means that it is directly on or above the other part, or that there may be other parts between them. In contrast, when a part is said to be "directly on" another part, there is no intervening part between them. Unless otherwise specified, % means % by weight, and 1 ppm is 0.0001% by weight. Unless otherwise defined, all terms, including technical and scientific terms, used herein have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. Terms defined in commonly used dictionaries are additionally interpreted as having a meaning consistent with the relevant technical literature and the present disclosure, and are not interpreted as having an ideal or very formal meaning unless otherwise defined. Hereinafter, the embodiments of the present invention will be described in detail so that a person of ordinary skill in the art to which the present invention belongs can easily carry out the present invention. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein.

[0018] According to an embodiment of the present invention, there is provided a binder for a secondary battery, comprising a water-soluble polymer and a conductive polymer, the water-soluble polymer comprising a first copolymer, the conductive polymer comprising a second copolymer and a polymer of a conductive monomer, the second copolymer having a degree of hydrolysis of 50% or more, and a peak at 3250 cm in an FT-IR spectrum. -1 Or 3350cm -1 The absorbance peak may be 22% or more.

[0019] The water-soluble polymer is added for the active material and electrode binding force, and the conductive polymer is added for improving the electrical conductivity of the binder. The binder for a secondary battery according to an embodiment of the present invention can obtain a functional binder with improved binding and electrical conductivity by using a mixture of a water-soluble polymer and a conductive polymer.

[0020] In the binder for a secondary battery according to an embodiment of the present invention, the conductive polymer may include a second copolymer and a polymer of a conductive monomer. By including the second copolymer and the polymer of a conductive monomer, dispersibility and electrical conductivity can be improved.

[0021] The second copolymer may have a degree of hydrolysis of 50% or more. Specifically, the second copolymer may have a degree of hydrolysis of 60% or more, more specifically, the second copolymer may have a degree of hydrolysis of 70% or more. If the degree of hydrolysis of the second copolymer is too low, the dispersibility of the conductive polymer produced may be low, resulting in poor stability of the slurry, which may cause problems such as reduced performance of the electrode.

[0022] In the binder for a secondary battery according to one embodiment of the present invention, the second copolymer has a peak at 3250 cm in the FT-IR spectrum. -1 Or 3350cm -1The absorbance peak appearing at 3250 cm in the FT-IR spectrum may be 22% or more. In the FT-IR spectrum, the magnitude of the peak can be quantified by the absorbance, the peak area, and the peak shape. Specifically, it can be said that the greater the absorbance (%) (=100%-transmittance (%)), the wider the peak area, and the sharper the peak shape, the greater the peak size. As the degree of hydrolysis of the second copolymer increases, the more polar functional groups such as -OH and -COOH are contained in the chain structure, and therefore the absorbance increases and the FT-IR spectrum at 3250 cm -1 Or 3350cm -1 The OH peak increases in the range of 3250 cm in the FT-IR spectrum. -1 Or 3350cm -1 The absorbance peak may be 23% or more.

[0023] The first copolymer may be a copolymer of a polymer containing a polar functional group and PAA, and the degree of hydrolysis may not be adjusted. By using a copolymer of a polymer containing a polar functional group and PAA as the first copolymer, the binding strength and dispersibility of the active material and the electrode are improved compared to the case of using PAA or PSS alone. Specifically, the first copolymer may be one or more selected from the group consisting of PVA-PAA, PEO-PAA, PPO-PAA, HEA-PAA, PHEA-PAA, PVP-PAA, PAM-PAA, PAN-PAA, PVAM-PAA, etc., whose degree of hydrolysis is not adjusted. More specifically, the first copolymer may be PVA-PAA, whose degree of hydrolysis is not adjusted. In addition, when a copolymer with a controlled degree of hydrolysis is used as the first copolymer, there is a possibility that a problem occurs in that the binding strength and dispersibility of the binder are reduced. In the case of a first copolymer with a controlled degree of hydrolysis, the degree of hydrolysis may be 0% to 10%.

[0024] The second copolymer may be a copolymer of a polymer containing a polar functional group and PAA, and may have an adjusted degree of hydrolysis. By using a copolymer of a polymer containing a polar functional group and PAA as the second copolymer, the binding force and dispersibility of the active material and the electrode are improved compared to the case of using PAA or PSS alone. Specifically, the second copolymer may be one or more selected from the group consisting of PVA-PAA, PEO-PAA, PPO-PAA, HEA-PAA, PHEA-PAA, PVP-PAA, PAM-PAA, PAN-PAA, and PVAM-PAA, each of which has an adjusted degree of hydrolysis. More specifically, the second copolymer may be PVA-PAA, each of which has an adjusted degree of hydrolysis. If a copolymer with an unadjusted degree of hydrolysis is used as the second copolymer, problems such as reduced dispersibility and electrical conductivity may occur.

[0025] The conductive monomer may be at least one selected from the group consisting of EDOT (3,4-Ethylenedioxythiophene), thiophene-based monomers, polyacetylene, polyaniline, and polypyrrole, but is not limited thereto. Specifically, the conductive monomer may be EDOT.

[0026] The conductive polymer may include the conductive monomer to the second water-soluble monomer in a weight ratio of 1:0.5 to 20. Specifically, the conductive monomer to the second water-soluble monomer may be included in a ratio of 1:0.5 to 10. More specifically, the conductive monomer to the second water-soluble monomer may be included in a ratio of 1:0.5 to 2. If the ratio of the second copolymer (PAA-x) is too low compared to the conductive monomer (EDOT), a problem of reduced electrical conductivity may occur. Conversely, if the ratio of the second copolymer is too high compared to the conductive monomer, a problem of reduced dispersibility may occur.

[0027] The ratio of the conductive polymer to the water-soluble polymer may be 4 to 6:1. If the ratio of the water-soluble polymer (PVA-PAA) is too low compared to the conductive polymer (PEDOT:PAA-x), the active material and electrode binding strength may be reduced. Conversely, if the ratio of the water-soluble polymer is too high compared to the conductive polymer, the electrical conductivity of the electrode may be reduced.

[0028] The slurry according to an embodiment of the present invention may include an electrode active material and the binder. The slurry according to an embodiment of the present invention may further include a solvent, a conductive material, etc., if necessary. Specifically, the slurry according to an embodiment of the present invention may include 95 to 99 wt % of the electrode active material and 1 to 5 wt % of the binder, based on 100 wt % of the total slurry. More specifically, the slurry according to an embodiment of the present invention may include 96 to 98 wt % of the electrode active material and 2 to 4 wt % of the binder, based on 100 wt % of the total slurry. If the content of the electrode active material is too low, a problem may occur in that the electrochemical performance of the battery is reduced, and if the content of the electrode active material is too high, a problem may occur in that the electrode cannot be manufactured (reduced binding force). In addition, if the content of the binder is too low, a problem may occur in that the adhesive force between the active material and the electrode is reduced, and if the content of the binder is too high, a problem may occur in that the resistance of the battery is increased.

[0029] The electrode active material may be a positive electrode active material or a negative electrode active material. The positive electrode active material may be any lithium-containing metal oxide that is commonly used in the art, without any restrictions. For example, one or more of composite oxides of lithium and a metal selected from cobalt, manganese, nickel, and combinations thereof may be used. Specific examples of the composite oxides include Li a A 1-b B 1 b D 12 (wherein, in the above formula, 0.90≦a≦1.8, and 0≦b≦0.5); Li a E 1-b B 1 b O 2-c D 1 c (wherein, 0.90≦a≦1.8, 0≦b≦0.5, and 0≦c≦0.05); LiE 2-b B 1 b O 4-c D 1 c (wherein 0≦b≦0.5 and 0≦c≦0.05);Li a Ni 1-b-c Co b B 1 c D 1 α (In the above formula, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2);Li a Ni 1-b-c Co b B 1 c O 2-α F 1 α (In the above formula, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2);Li a Ni 1-b-c Co b B 1 c O 2-α F 1 2 (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mn b B 1 c D 1 α (In the above formula, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2);Li a Ni 1-b-c Mn b B 1 c O 2-α F 1 α(In the above formula, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2);Li a Ni 1-b-c Mn b B 1 c O 2-α F 1 2 (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni b E c G d O2 (wherein 0.90≦a≦1.8, 0≦b≦0.9, 0≦c≦0.5, and 0.001≦d≦0.1); Li a Ni b Co c Mn d G e O2 (wherein, 0.90≦a≦1.8, 0≦b≦0.9, 0≦c≦0.5, 0≦d≦0.5, and 0.001≦e≦0.1); Li a NiG b O2 (wherein 0.90≦a≦1.8 and 0.001≦b≦0.1 in the above formula); Li a CoG b O2 (wherein 0.90≦a≦1.8 and 0.001≦b≦0.1 in the above formula); Li a MnG b O2 (wherein 0.90≦a≦1.8 and 0.001≦b≦0.1 in the above formula); Li a Mn2G b O4 (wherein 0.90≦a≦1.8 and 0.001≦b≦0.1 in the above formula); QO2; QS2; LiQS2; V2O5; LiV2O5; LiI 1 O2;LiNiVO4;Li (3-f) J2(PO4)3(0≦f≦2);Li (3-f) A compound represented by any one of the chemical formulas Fe2(PO4)3(0≦f≦2);LiFePO4 can be used.

[0030] In the above formula, A is Ni, Co, Mn, or a combination thereof; B 1is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements or combinations thereof, and D 1 is O, F, S, P, or a combination thereof, E is Co, Mn, or a combination thereof, and F 1 is F, S, P, or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; Q is Ti, Mo, Mn, or a combination thereof; I is Cr, V, Fe, Sc, Y, or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu, or a combination thereof.

[0031] Specifically, LiCoO2, LiMn x O 2x (x=1, 2), LiNi 1-x Mn x O 2x (0 <x<1)、LiNi 1-x-y Co x Mn y O2(0≦x≦0.5, 0≦y≦0.5), LiFePO4, etc.

[0032] Of course, the compound may have a coating layer on its surface, or the compound may be mixed with a compound having a coating layer. The coating layer may include a coating element compound such as an oxide, hydroxide, oxyhydroxide, oxycarbonate, or hydroxycarbonate of a coating element. The compound forming the coating layer may be amorphous or crystalline. The coating element included in the coating layer may be Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The coating layer forming step may use any coating method that can coat the compound using these elements in a manner that does not adversely affect the physical properties of the positive electrode active material (e.g., spray coating, immersion method, etc.), and this is well understood by those who are engaged in the field, so a detailed explanation will be omitted.

[0033] The negative electrode active material may be any material that can be used as a negative electrode active material for lithium secondary batteries in the art, and may include, for example, at least one selected from the group consisting of lithium metal, metals capable of forming an alloy with lithium, transition metal oxides, non-transition metal oxides, and carbonaceous materials.

[0034] Specifically, the metals capable of alloying with lithium may be Si, Sn, Al, Ge, Pb, Bi, Sb, Si-Y alloy (wherein Y is an alkali metal, alkaline earth metal, Group 13 element, Group 14 element, transition metal, rare earth element or a combination of these elements and is not Si), Sn-Y alloy (wherein Y is an alkali metal, alkaline earth metal, Group 13 element, Group 14 element, transition metal, rare earth element or a combination of these elements and is not Sn), etc. The element Y may be Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, or Te.

[0035] Specifically, the transition metal oxides may be lithium titanate, vanadium oxide, lithium vanadate, etc.

[0036] Specifically, the non-transition metal oxides may be SnO2, SiO x (0 < x < 2), etc.

[0037] Specifically, the carbon-based materials may be crystalline carbon, amorphous carbon or a mixture thereof. The crystalline carbon may be graphite such as amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, and the amorphous carbon may be soft carbon (low-temperature calcined carbon) or hard carbon, mesophase pitch carbide, calcined coke, etc. More specifically, the carbon-based material may be Graphite.

[0038] As the solvent, N-methylpyrrolidone, acetone, water, etc. can be used, but are not limited thereto, and any solvent that can be used in the technical field can be used.

[0039] The conductive material may be, but is not limited to, carbon black, graphite fine particles, or the like, and any material that can be used as a conductive material in the art may be used.

[0040] An electrode according to an embodiment of the present invention may be formed by applying the above-described slurry onto the surface of a current collector and drying it.

[0041] A secondary battery according to an embodiment of the present invention includes a positive electrode, a negative electrode, an electrolyte interposed therebetween, and a separator interposed between the positive electrode and the negative electrode, and at least one selected from the positive electrode and the negative electrode may be the above-mentioned electrode.

[0042] The separator may be any one that is generally used in lithium batteries. It may have low resistance to the ion movement of the electrolyte and excellent moisture absorption capacity of the electrolyte. Specifically, it may be selected from glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), or a combination thereof, and may be in the form of a nonwoven fabric or a woven fabric. Specifically, a rollable polyolefin separator such as polyethylene or polypropylene may be used for a lithium ion battery, and a separator that has excellent impregnation capacity of an organic electrolyte may be used for a lithium ion polymer battery.

[0043] The electrolyte may be an organic electrolyte solution, which may be prepared by dissolving a lithium salt in an organic solvent.

[0044] The organic solvent may be any one that can be used as an organic solvent in the technical field.Specifically, it may include one or more selected from the group consisting of ethyl methyl carbonate (EMC), methyl propyl carbonate, ethyl propyl carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, propylene carbonate (PC), ethylene carbonate (EC), fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), butylene carbonate, ethyl propionate, ethyl butyrate, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, gamma-valerolactone, gamma-butyrolactone and tetrahydrofuran, but is not limited thereto, and any one that can be used as an organic solvent in the technical field may be used.

[0045] Any lithium salt that can be used as a lithium salt in the art can be used. Specifically, LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (where x and y are natural numbers), LiCl, LiI, or a mixture thereof.

[0046] The electrolyte may be a solid. Specifically, the electrolyte may be, but is not limited to, boron oxide, lithium oxynitride, or the like, and any electrolyte that can be used as a solid electrolyte in the art may be used. The solid electrolyte may be formed on the negative electrode by a method such as sputtering.

[0047] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the embodiments set forth herein. EXAMPLES

[0048] [Production Example - Synthesis and Hydrolysis of PVA-PAA Polymer]

[0049] (1) Synthesis of PVA-PAA polymers with uncontrolled hydrolysis

[0050] A reactor was charged with 1050g of distilled water as a solvent and 10g of emulsifier (dowfax), and after stirring for 1 hour under a nitrogen atmosphere, 2.5g of initiator (KPS, potassium persulfate) was added. 140g of vinyl acetate and 350g of ethyl acrylate as monomers were dropped into the reactor for 3 hours, and polymerization was carried out at 65°C for 1 hour to produce a PVA-PAA (Polyvinylacetate-Polyethylacrylate) copolymer. (Hereinafter, PVA-PAA copolymer with an unadjusted degree of hydrolysis will be referred to as "PVA-PAA".)

[0051] (2) Hydrolysis of PVA-PAA polymer

[0052] PVA-PAA was hydrolyzed using 150g of ethanol and 17g of NaOH (sodium hydr oxide) at 65℃ while adjusting the hydrolysis reaction time. The hydrolyzed PVA-PAA was dissolved in distilled water and washed several times to produce a hydrolyzed PVA-PAA copolymer. (Hereinafter, according to the degree of hydrolysis, a PVA-PAA copolymer with a hydrolysis degree of 30% is called "PAA-1", a PVA-PAA copolymer with a hydrolysis degree of 70% is called "PAA-3", and a PVA-PAA copolymer with a hydrolysis degree of 90% is called "PAA-5".)

[0053] [Example 1]

[0054] (1) Manufacturing of conductive polymer binder

[0055] Using 300g of water as a solvent, 5g of the solid content of PAA-3, the receptor prepared in the above preparation example, and 5g of EDOT (ethylenedioxythiophene), a conductive monomer, were mixed in a 1:1 ratio, and 10g of an initiator (APS, ammonium persulfate) was added to prepare a conductive polymer binder "PEDOT:PAA-3".

[0056] (2) Preparation of slurry

[0057] 97 wt% of graphite as an electrode active material, 2.5 wt% of PVA-PAA as a binder, and 0.5 wt% of PEDOT:PAA-3 were mixed and then added to distilled water and stirred with a mechanical stirrer to prepare a slurry.

[0058] (3) Electrode (negative electrode) manufacturing

[0059] The prepared slurry was applied to a 10 μm copper foil film, which is a negative electrode current collector, to a thickness of 300 to 400 μm, dried in a hot air dryer at 110° C. for 1 hour, and then rolled with a roll press to prepare a negative electrode.

[0060] (4) Manufacture of secondary batteries

[0061] The positive electrode, electrolyte (non-aqueous electrolyte containing lithium) and separator used in the secondary battery production were purchased and used as NCM 622 (Wellcos Co., Ltd., Korea), 1M LiPF6 DEC / EC+FEC 1% (Seoulbrain, Korea) and polyolefin separator Celgard 2325 (Celgard, USA), respectively. A lithium secondary battery was produced using the negative electrode produced in (3) above, the positive electrode, electrolyte and separator.

[0062] [Example 2]

[0063] In the preparation of the conductive polymer binder, the PAA-5 prepared in the above Preparation Example was used as a receptor to prepare "PEDOT:PAA-5", but the conductive polymer, slurry, electrode and secondary battery were prepared in the same manner as in Example 1.

[0064] [Comparative Example 1]

[0065] The slurry, electrodes, and secondary batteries were manufactured in the same manner as in Example 1, except that the slurry was manufactured using 97 wt % graphite as the electrode active material and 3.0 wt % PVA-PAA as the binder, and did not contain a conductive polymer.

[0066] [Comparative Example 2]

[0067] In the preparation of the conductive polymer binder, PAA(aldrich) was used as an acceptor to prepare "PEDOT:PAA", but the conductive polymer, slurry, electrode and secondary battery were prepared in the same manner as in Example 1.

[0068] [Comparative Example 3]

[0069] In the preparation of the conductive polymer binder, the PAA-1 prepared in the above Preparation Example was used as a receptor to prepare "PEDOT:PAA-1", but the conductive polymer, slurry, electrode and secondary battery were prepared in the same manner as in Example 1.

[0070] [Experimental Example 1]

[0071] The degree of hydrolysis of PAA-1 and PAA-5 prepared in the above Preparation Examples was confirmed by FT-IR and is shown in Figure 1. As the degree of hydrolysis increases, the chain structure contains more polar functional groups such as -OH and -COOH, and therefore PAA-5, which has a higher degree of hydrolysis, has a peak at 3300 cm higher than PAA-1. -1 It was confirmed that the magnitude of the OH peak near

[0072] [Experimental Example 2]

[0073] To examine the dispersion safety of conductive polymers depending on the degree of hydrolysis, the conductive polymer binders of Example 2 and Comparative Example 2 were placed in empty cans and observed for stability and the presence or absence of phase separation for 15 days at 25°C, and the results are shown in Figure 2. It was confirmed that Example 2, which used a receptor adjusted to have a high degree of hydrolysis, showed excellent dispersion stability without phase separation, but Comparative Example 2, which used a receptor with an unadjusted degree of hydrolysis, showed poor dispersion stability and phase separation occurred.

[0074] [Experimental Example 3]

[0075] The slurries of Comparative Example 1, Comparative Example 2, Example 1, and Example 2 were visually observed and compared, and the dispersion stability was evaluated using a grind gauge, as shown in FIG. 3. The viscosities of Example 1 and Example 2, which contain conductive polymers, were visually compared with Comparative Example 1, which does not contain conductive polymer material, and it was confirmed that the viscosity of the slurries did not increase or decrease. This showed that the conductive polymer material did not affect the viscosity of the slurry. Also, as shown in FIG. 3, in the case of Example 1 and Example 2, which contain conductive polymers, no particles were observed even at 30 μm or less on the grind gauge, so it was confirmed that they exhibited excellent slurry dispersion stability. However, in the case of Comparative Example 2, particles were observed at 90 μm or more, so it was confirmed that the slurry dispersion stability was poor. This is believed to be due to the fact that the dispersion safety of the conductive polymer binder was reduced by using a receptor with an unadjusted degree of hydrolysis in the production of the conductive polymer.

[0076] [Experimental Example 4]

[0077] The electrical conductivity of the electrodes manufactured in the Examples and Comparative Examples was measured using a sheet resistance meter, and is shown in the following Table 1. In addition, the lithium secondary batteries manufactured in the Examples and Comparative Examples were charged and discharged five times under charging conditions (0.1-0.5C) and discharging conditions (0.1-0.5C) at 25° C., and the battery resistance and battery life characteristics (≧500 cycles) were evaluated under the condition of SOC 50%, and are shown in the following Table 1.

[0078] [Table 1]

[0079] As shown in Table 1, the electrodes of Examples 1 and 2 containing a conductive polymer prepared using an acceptor satisfying the range of hydrolysis of the present invention have excellent electrical conductivity compared to the electrodes of Comparative Examples 1 to 3 which do not contain a conductive polymer, use an acceptor with an uncontrolled degree of hydrolysis, or use an acceptor not satisfying the range of hydrolysis of the present invention. In addition, it can be confirmed that the secondary batteries of Examples 1 and 2 have improved battery characteristics, with a reduced battery resistance and an increased battery life, compared to the comparative example. Comparing Comparative Example 3, Examples 1 and 2, it can be confirmed that the electrical conductivity, battery resistance and battery life characteristics of the electrode improve as the degree of hydrolysis of the acceptor increases, and therefore, it can be seen that the dispersibility of the conductive polymer binder improves as the degree of hydrolysis increases, resulting in a uniform distribution in the electrode and an increased electrical conductivity, which affects the performance improvement of the secondary battery.

[0080] [Experimental Example 5]

[0081] The lithium secondary batteries of Comparative Example 1, Comparative Example 2, Example 1, and Example 2 were fabricated in the form of a coin cell 2032, and then charged / discharged under the same conditions as in Experimental Example 4. The battery resistance was measured by an EIS method. The results of the electrochemical evaluation are shown in FIG. 4.

[0082] In the case of Examples 1 and 2, similar to the internal resistance results of Experimental Example 4, it was confirmed that the resistance was significantly reduced compared to Comparative Examples 1 and 2, and that the degree of reduction in resistance was greater as the degree of hydrolysis of the receptor increased.

[0083] The present invention is not limited to the embodiments, and can be manufactured in various different forms, and a person having ordinary skill in the art to which the present invention pertains can understand that the present invention can be embodied in other specific forms without changing the technical concept or essential features of the present invention. Therefore, it should be understood that the embodiments described above are illustrative in all respects and are not limiting.

Claims

1. A water-soluble polymer and a conductive polymer are included, the water-soluble polymer comprises a first copolymer, the conductive polymer comprises a second copolymer and a polymer of a conductive monomer; The second copolymer has a degree of hydrolysis of 50% or more and has a peak at 3250 cm in the FT-IR spectrum. -1 or 3,350 cm -1 The binder for a secondary battery has an absorbance peak of 22% or more.

2. The binder for secondary batteries according to claim 1 , wherein the first copolymer is a copolymer of a polymer containing a polar functional group and PAA, and the degree of hydrolysis is not adjusted.

3. 2. The binder for a secondary battery according to claim 1, wherein the first copolymer is a PVA-PAA copolymer having an uncontrolled degree of hydrolysis.

4. The binder for a secondary battery according to claim 1 , wherein the second copolymer is a copolymer of a polymer containing a polar functional group and PAA, and has a controlled degree of hydrolysis.

5. 2. The binder for a secondary battery according to claim 1, wherein the second copolymer is a PVA-PAA copolymer with a controlled degree of hydrolysis.

6. 2. The binder for a secondary battery according to claim 1, wherein the conductive monomer is at least one selected from the group consisting of 3,4-ethylenedioxythiophene (EDOT), a thiophene-based monomer, polyacetylene, polyaniline, and polypyrrole.

7. The conductive polymer is 2. The binder for a secondary battery according to claim 1, comprising a weight ratio of the conductive monomer to the second copolymer of 1:0.5-20.

8. 2. The binder for a secondary battery according to claim 1, wherein the ratio of the conductive polymer to the water-soluble polymer is 4 to 6:

1.

9. A slurry comprising an electrode active material and the binder according to claim 1 .

10. Based on 100% by weight of the total slurry, The electrode active material comprises 95 to 99% by weight, 10. The slurry of claim 9 comprising 1 to 5% by weight of said binder.

11. An electrode formed by applying the slurry according to claim 9 onto a surface of a current collector and drying the slurry.

12. The battery includes a positive electrode, a negative electrode, an electrolyte interposed therebetween, and a separator interposed between the positive electrode and the negative electrode; A secondary battery, wherein at least one selected from the positive electrode and the negative electrode is the electrode according to claim 11.

Citation Information

Patent Citations

  • Conductive composite waterborne adhesive as well as one-pot preparation method and application thereof

    CN107663428A

  • Binder composition for power storage device, slurry for power storage device electrode, power storage device electrode and power storage device

    JP2016134241A

  • Positive electrode for nonaqueous electrolyte secondary battery, manufacturing method therefor, and nonaqueous electrolyte secondary battery

    JP2017004764A